2018
DOI: 10.1021/acs.analchem.8b01384
|View full text |Cite
|
Sign up to set email alerts
|

Highly Bright Self-Assembled Copper Nanoclusters: A Novel Photoluminescent Probe for Sensitive Detection of Histamine

Abstract: In this work, highly photoluminescent (PL) self-assembled copper nanoclusters (Cu NCs) capable of rapid, sensitive, and selective detection of histamine were developed. Cu NCs were synthesized in facile conditions by using 2,3,5,6-tetrafluorothiophenol (TFTP) as both the reducing agent and the protecting ligand, which exhibited intense saffron yellow (590 nm) PL via self-assembled induced emission (SAIE), and the absolute quantum yield (QY) of assembly was as high as 43.0%. The size, electronic states, and mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(47 citation statements)
references
References 58 publications
1
46
0
Order By: Relevance
“…Ailing Han et al have prepared 2,3,5,6tetrafluorothiophenol (TFTP)-protected CuNCs with selfassembled induced emission (SAIE) properties (QY 43%) and tested it for histamine sensing. 229 The developed sensor could detect histamine at its lowest concentration of 60 nM in the range of 0.1-10 μM. Furthermore, the histamine detection sensitivity was increased twice (LOD 30 nM) when Dpenicillamine-CuNCs were applied as a fluorometric sensor with AIE enhancement properties.…”
Section: Neurotransmitter Detectionmentioning
confidence: 95%
See 1 more Smart Citation
“…Ailing Han et al have prepared 2,3,5,6tetrafluorothiophenol (TFTP)-protected CuNCs with selfassembled induced emission (SAIE) properties (QY 43%) and tested it for histamine sensing. 229 The developed sensor could detect histamine at its lowest concentration of 60 nM in the range of 0.1-10 μM. Furthermore, the histamine detection sensitivity was increased twice (LOD 30 nM) when Dpenicillamine-CuNCs were applied as a fluorometric sensor with AIE enhancement properties.…”
Section: Neurotransmitter Detectionmentioning
confidence: 95%
“…228 For instance, Shuo Wang and co-workers showed that nanoribbons of CuNCs can be directly formed from the reduction of the copper ions in the presence of 2,3,5,6-tetrafluorothiophenol (TFTP) as both the reducing agent and the protecting ligand at 20 °C. 229 The TEM imaging revealed highly ordered nanoribbons with an approximate width of about 20 nm, a length about 400−800 nm, and a thickness of about 15 nm, emitting a strong yellow luminescence upon UV irradiation (QY 43%). Hao Zhang and co-workers showed that the spherical dodecanethiol (DT)-capped CuNCs with the size of 1.9 nm selfassemble into ribbons (average width about 50−200 nm, length about 1−2 um, and thickness about 13.5 nm) at 128 °C ( Fig.…”
Section: Self-assembly Of Clusters and Contribution Of Metal Defectsmentioning
confidence: 99%
“…On the basis of the advantages of the aromatic-thiol-capped Cu NCs, replacing the conventional alkyl thiols with aromatic ones as reducing and capping agents to synthesize self-assembled Cu NCs has a great effect on LMCT and LMMCT, resulting in emission enhancement and emission color tunability. For example, utilizing 2,3,5,6-tetrafluorothiophenol (TFTP) as a reducing and capping agent, self-assembled nanoribbons of Cu NCs were easily synthesized, for which the absolute quantum yield (QY) was as high as 43.0% [59]. Additionally, by using different aromatic thiols with varied conjugation capabilities as capping ligands, the emission color of NC assemblies can be tuned from yellow to dark red and their QY can reach as high as 15.6% [60].…”
Section: The Self-assembly Of Cu Ncsmentioning
confidence: 99%
“…[44] A highly QYs (43.0 %) CuNCs with self-assembled induced emission (SAIE) was developed by one-step preparation of mixing TFTP (2, 3, 5, 6-tetrafluorothiophenol) with Cu(NO 3 ) 2 in ethanol and the as-prepared CuNCs was sensitive to the assay of histamine. [45] Later, Basu et al used a simple and stabilizer-free chemical reduction method for the gram-scale synthesis of CuNCs with 15 days stability by cheap metal precursor copper acetate and stabilizing the CuNCs by a thiol containing proteinaceous amino acid cysteine. [28] Cu 2 + induced 3-mercaptopropionic acid functionalized copper nanoclusters (Cu 2 + @MPA-CuNCs, QYs = 4.8 %) was developed by a one-pot reaction as a fluorescent probe for the sulfide ion assay with a LOD of 26.3 nM.…”
Section: Introductionmentioning
confidence: 99%